FORMATION OF A PROFESSIONAL ORIENTATION OF THE FUTURE TEACHER DURING THE ORGANIZATION OF EDUCATIONAL PROCESS AT PEDAGOGICAL UNIVERSITY (Pedagogy of Higher and Secondary Education, 2022)
The article deals with significance of pedagogical focus as an important component of future teachers ’ professional and pedagogical training
Keywords: pedagogical activity; professional-pedagogical orientation; teaching and educational process